Efek Kualitas Produk, Harga dan Brand Terhadap Keputusan Pembelian Sepeda Polygon Saat Pandemi Covid-19 di Kota Batam - Auzar, Silvia Revana; Surbakti, Ferdi Armando (Zona Manajerial: Program Studi Manajemen (S1), 2022)
This study aims to examine and analyze the effect of Product Quality, Price and Brand on Polygon Bicycle Purchase Decisions in the Batam City Pandemic Era. The results of this study tested the effect of product quality on purchasing decisions using t-test with a significance level of 0.05, obtained p-value of 0.047 <0.05, then reject H_0. This shows that there is a positive and significant effect of product quality on purchasing decisions for polygon bicycles in the Batam City pandemic era. The results of the analysis using the t-test obtained a p-value of 0.034 <0.05 then reject H_0. These results indicate that in this study the price has a positive and significant effect on purchasing decisions for polygon bicycles in the Batam City pandemic era. The results of the job satisfaction test with the t-test obtained a p- value of 0.000 <0.05, then rejecting H_0 it can be said that there is a positive and significant influence on the decision to purchase polygon bicycles in the Batam City pandemic era. In this study, simultaneously testing using the F test with a significance level of 0.05 obtained a p-value of 0.000 then reject H_0. The results of this study indicate that the variables of product quality, price and brand together will affect purchasing decisions.